(untitled) (Annals of Medical Research, 2021)
Aim: The main purpose of this study was to examine how a change in thiol/disulfide balance, which plays a significant role in cellular activities like detoxification, antioxidant protection, apoptosis, and cell growth, affects fibromyalgia (FM) patients.Material and Methods: This study was executed in two groups, included 46 female FM patients and 46 healthy female subjects. The American College of Rheumatology (ACR) standard was used to diagnose patients with fibromyalgia. The automated measurement method was used to examine the native thiol-disulfide exchanges in both groups.Results: After determining the parameters of thiol/disulphide balance for groups, it was discovered that the mean total thiol (p = 0.009), native thiol levels (p = 0.001), native thiol/total thiol (p 0.001) percent ratios were higher in control group than FM group. Conversely, the disulphide levels (p = 0.026), disulphide/native thiol percent ratios (p 0.001), disulphide/total thiol percent ratios (p 0.001) were lower in control group than FM group.Conclusion: The study demonstrates that the thiol/disulfide equilibrium could be a new oxidative stress marker that can be used for FM. However, it is considered that there needs to be more confirmatory studies to use thiol/disulfide balance in fibromyalgia as a stress marker.